ANALISIS PENGGUNAAN INOKULAN LEGIN DAN TEKNOLOGI PANGKAS PUCUK TERHADAP PRODUKTIVITAS KEDELAI - Sucahyo, Anang; Wijayanto, Budi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2018)
The Legin (Leguminosae inoculum) application is a technology by mixing Rhizobium inoculants with soybean seeds at the time of planting. The goal is when the existing soybean seeds of the surrounding Rhizobium japanicum bacteria will be symbiotic with the soybean roots. The Rhizobium japanicum bacteria can be isolated from effective symbiotic soybean root nodules, then cultured and can be used as inoculants mixed with peat soil. While cutting shoots done by breaking the apical dominance so that pruning effect on plant growth with the aim of encouraging plants to branch off much and produce new shoots, so as to obtain maximum results. This study examines the application of legin and shoot cutting technology on soybean cultivation. Soybean varieties used are varieties of anjasmara. The results of this study indicate that the application of legin and shoot can increase the production of 1.74 tons / ha.